ON THE PECULIARITIES OF THE NEW HUNGARIAN CRIMINAL PROCEDURE ACT - Fantoly, Zsanett (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
This paper is focusing on the fundamental changes brought by the Hungarian Criminal Procedure Act [Act XC of 2017], which entered into force on 1st of July 2018. New or renewed legal constructs of the criminal procedure are being reviewed. These range from the introduction of a split model of the investigation, to the introduction of two ways of cooperation with the defendant and affect several legal institutions. The new procedural act brings a completely new approach to the parties’ right of disposal, the extension of the victim’s rights, the secret information gathering, and many other issues. The author seeks to capture those provisions of the act that fundamentally define and reflect this new image of the criminal procedure.